Every 1,000 steps matter: incremental reductions in metabolic syndrome risk in Japanese office workers - Yukako Yamaga; Thomas Svensson; Ung-il Chung; Akiko Kishi Svensson (Diabetology & Metabolic Syndrome)
Abstract Background Several studies have investigated the association between metabolic syndrome (MetS) and physical activity (PA). However, further research is needed using objective measures of PA in free-living conditions, while also accounting for the time-variant nature of MetS. This study aimed to: (1) investigate the association between wearable device-measured step count and 5-year MetS incidence in generally healthy Japanese participants, using annual health check-up (AHC) data and interval-censored survival analysis; and (2) assess the current, and recently revised, reference value (8,000 steps/day) of Japan’s Ministry of Health, Labour and Welfare (MHLW), and (3) investigate the possibility of non-linear associations between daily step count and MetS. Methods This longitudinal prospective observation study identified average daily step count per year/person as the main exposure, and MetS incidence, defined according to Japanese guidelines, as the main outcome. The main analysis included 730 participants without MetS or pre-MetS at baseline. An interval-censored Cox model was applied to assess MetS incidence using time-to-event data. Results Every 1,000 steps added to the average step count was significantly and inversely associated with incident MetS in adjusted models [Model 1: HR = 0.92; 95% CI: 0.85, 1.00; Model 2: HR = 0.91; 95% CI: 0.83, 0.99] (p < 0.05). The current reference value (8,000 steps/day) also indicated a significant inverse association [Model 1: HR = 0.32; 95% CI: 0.14, 0.71; Model 2: HR = 0.26; 95% CI: 0.11, 0.61] (p < 0.01). Higher daily step counts lowered the risk of MetS incidence according to the amount of steps up to a step count of 12,000, however, the dose-response effect was attenuated beyond 12,000 steps/day. Conclusions Each additional 1,000 daily steps was associated with a 9% reduction in the risk of developing MetS among healthy participants. The reference value (8,000 steps/day) was associated with a 74% reduction in MetS risk.